From Guest to Host Religion: The Transformation of Islam In Papua - Nur, Syamsudin; Ernas, Saidin; Rumra, Moh. Yamin; Wakano, Abidin; Kamarzaman, Mohd Haidhar (Pascasarjana IAIN Pontianak, 2025)
This article examines the dynamics of Islamic da’wah in Papua, highlighting historical challenges and contemporary transformations within a social, political, and cultural context. This study uses a qualitative approach with historical and social analysis through a review of literature, Islamic organizational documents, and narratives from Papuan Muslim figures. The results show that although Islam was the first Abrahamic religion to arrive in Papua, its spread was hampered by the influence of colonialism and the dominance of Christian and Catholic missions, which relegated Islam to a minority position with an exclusive image. However, over time, Islamic da’wah has undergone significant transformation, particularly through educational and empowerment initiatives undertaken by organizations such as Nahdlatul Ulama, Muhammadiyah, and the Papuan Muslim Council. These changes have fostered the emergence of educated and influential Papuan Muslim figures and strengthened awareness of Islamic identity as an integral part of Papuan culture. These findings confirm that Islamic preaching based on a cultural approach and social empowerment is more effective in transforming the old narrative of Islam as a “newcomer religion,” toward recognizing it as a legitimate part of Papuan identity. Going forward, ethnographic-based research is needed to capture the pulse of Papuan Muslims at the grassroots level and understand Islam as growing from within, not simply coming from the outside.